SPORT, STATE AND CONSTITUTION: A STUDY ABOUT EDUCATIONAL AND FUNDAMENTAL SPORT IN BRAZIL (Fiep Bulletin - online, 2016)
In the Brazilian state, the sport is expected and guaranteed by, Article 217 of the Constitution. From this premise, the study seeks to identify the situation of sport education and grassroots, national, in the light of relevant legislation and its own bibliography of events held on the topic, and also in the context of the current National Policy on Sport. Makes a specific approach: the Educational Sports, the Sports Incentive Law and the Second Half Program. We conclude that even though, both covered legally, require more effective, permanent and comprehensive public policies that opportunism greater access of the population to sports practices.
Keywords: Sport education. Base sport. Constitution. .